2013
DOI: 10.3928/01477447-20121217-23
|View full text |Cite
|
Sign up to set email alerts
|

Modified Plate-only Open-door Laminoplasty Versus Laminectomy and Fusion for the Treatment of Cervical Stenotic Myelopathy

Abstract: The purpose of this study was to compare modified plate-only laminoplasty and laminectomy and fusion to confirm which of the 2 surgical modalities could achieve a better decompression outcome and whether a significant difference was found in postoperative complications. Clinical data were retrospectively reviewed for 141 patients with cervical stenotic myelopathy who underwent plate-only laminoplasty and laminectomy and fusion between November 2007 and June 2010. The extent of decompression was assessed by mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
89
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 37 publications
3
89
0
3
Order By: Relevance
“…This different result in the subgroup analysis was caused by the relative weighting of the studies in the overall versus the long-term follow-up analysis. In the overall analysis, the studies of Zhang et al 19 and Lee et al 10 had very low weights (less than 2% for each), whereas in the long-term follow-up analysis they were weighted almost equally with the study of Yang et al 18 (approximately 30% each). The reason for this difference was that the study by Woods et al, 17 which had a very narrow standard deviation, was excluded in the long-term follow-up analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This different result in the subgroup analysis was caused by the relative weighting of the studies in the overall versus the long-term follow-up analysis. In the overall analysis, the studies of Zhang et al 19 and Lee et al 10 had very low weights (less than 2% for each), whereas in the long-term follow-up analysis they were weighted almost equally with the study of Yang et al 18 (approximately 30% each). The reason for this difference was that the study by Woods et al, 17 which had a very narrow standard deviation, was excluded in the long-term follow-up analysis.…”
Section: Discussionmentioning
confidence: 99%
“…5,11 Other studies addressing the superiority of one technique over the other have shown controversial results. 1,12,18,19 The aim of the present study was to compare improvements in myelopathy, the development of postoperative kyphosis, and the prevalence of axial pain in patients undergoing EL or LF by using a meta-analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Excellent longterm results have been reported using this technique [3][4][5][6][7]. Clinical follow-up studies have shown that laminoplasty generally results in greater patient satisfaction and lower complication rates than laminectomy [8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…These studies were designed to compare the efficacy and complication rates between 2 different surgical interventions or varying techniques. Studies reported on differences between anterior and posterior approaches (n = 9); 15,18,19,22,30,42,44,48,59 laminoplasty and laminectomy and fusion (n = 4); 10,19,70,72 anterior decompression and Bryan disc (n = 1); 11 and anterior cervical discectomy and fusion (ACDF) and corpectomy (n = 2). 47,63 In addition, 11 studies compared laminoplasty techniques or considered technical differences such as laminoplasty with and without foraminotomy or muscle preservation.…”
Section: Study Characteristicsmentioning
confidence: 99%